Efficacy and Safety of Subthreshold Micropulse Yellow Laser for Persistent Diabetic Macular Edema After Vitrectomy: A Pilot Study - Bonfiglio, Vincenza; Rejdak, Robert; Nowomiejska, Katarzyna; Zweifel, Sandrine Anne; Justus Wiest, Maximilian Robert; Romano, Giovanni Luca; Bucolo, Claudio; Gozzo, Lucia; Castellino, Niccolò; Patane, Clara; Pizzo, Corrado; Reibaldi, Michele; et al. (Frontiers in Pharmacology, 2022)
To examine the effect of subthreshold micropulse yellow laser (SMYL) on best-corrected visual acuity (BCVA), foveal macular thickness (FMT) and optical coherence tomography angiography (OCT-A) changes in eyes with persistent diabetic macular edema (DME) after pars plana vitrectomy (PPV) for tractional DME (TDME). Fifty-four eyes (54 consecutive patients) with persistent DME were prospectively enrolled. BCVA, FMT by OCT were analysed at baseline, 3 and 6 months. Additionally, following parameters such as the vessel density (VD) in the superficial capillary plexus (SCP) and deep capillary plexus (DCP) respectively, and the area of foveal avascular zone (FAZ) were also evaluated on OCT-A. All patients had diabetes mellitus Type 2 (mean age, 69.65 ± 11.30 years; duration of diabetes mellitus, 14.7 ± 8.7 years; and HbA1c 8.1 ± 2.1%). Mean BCVA was significantly different [F(2,106) = 17.25; p<0.001; η_p^2=0.246] at baseline 51.54 ±13.81 ETDRS letters, 57.81 ±12.82 at 3 months (p<0.001) and 57.83 ±13.95 at 6 months (p<0.001), respectively. Mean FMT significantly decrease [F(2,106)=30.98; p<0.001; η_p^2 = 0.368] from baseline value 410.59 ± 129.91 μm to 323.50 ± 89.66 μm at 3 months (p<0.001) and to 283.39 ± 73.45 μm at 6 months (p<0.001); statistically differences in FMT values between 3 and 6 months was also present (p=0.012). There was no statistically significant change in any other OCT angiography. There were no adverse treatment effects. SMYL may reduce macular thickening and improve BCVA in eyes with persistent macular edema after PPV and membrane peeling for TDME.